2011
DOI: 10.1016/j.limno.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of anthropogenic salt-load on the aquatic Fauna: A synthesis of 17 years of biological survey on the rivers Werra and Weser

Abstract: a b s t r a c tThe reduction and the smoothened amplitudes of the chloride concentrations since 2000 have resulted in a gradual positive development of the aquatic fauna in the River Werra. In the salinized section of the river increasing species numbers have been determined along the salinity gradient, which shows maximum chloride concentrations of about 2500 mg/l, maximum potash concentrations at approximately 200 mg/l, and magnesia concentrations peaked at 320 mg/l. As an immediate consequence of the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 7 publications
(7 reference statements)
4
39
0
Order By: Relevance
“…Salt pollution also had clear effects on the aquatic macroinvertebrate communities, as had been previously reported for streams affected by potash mining in the Werra River basin (Bäthe and Coring, 2011;Braukmann and Böhme, 2011) and for the Llobregat River (Prat et al, 1983;Prat and Rieradevall, 2006). Taxa richness strongly responded to salinization, with only 7 taxa being registered in site P4 (conductivity=11.0 mS cm -1…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Salt pollution also had clear effects on the aquatic macroinvertebrate communities, as had been previously reported for streams affected by potash mining in the Werra River basin (Bäthe and Coring, 2011;Braukmann and Böhme, 2011) and for the Llobregat River (Prat et al, 1983;Prat and Rieradevall, 2006). Taxa richness strongly responded to salinization, with only 7 taxa being registered in site P4 (conductivity=11.0 mS cm -1…”
Section: Discussionsupporting
confidence: 72%
“…Secondary salinization has many different causes, with agriculture and mining being the most important (Cañedo-Argüelles et al, 2013). One of the mining activities directly related to freshwater salinization is potash mining, which has been especially intense in some European regions as the Werra Basin in Germany (Bäthe and Coring, 2011;Braukmann and Böhme, 2011) or the Llobregat Basin in Spain (Gorostiza, 2014). Here we focus on the latter to assess the potential impact of potash mining on the biological quality of rivers and streams.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity largely influences the distribution of macroinvertebrates in the river Lippe and presumably acts as an overarching stressor to limit the distribution of macroinvertebrates (Bäthe and Coring, 2011;Braukmann and Böhme, 2011).…”
Section: Indicator Taxa and Salinity Thresholds For Macroinvertebratesmentioning
confidence: 99%
“…Among them, the caddis larvae Psychomyia pusilla (salinity threshold value of 1612 S/cm) and the gastropod Ancylus fluviatilis (salinity threshold value of 1098 S/cm) have previously been characterized to prefer water with low salinity (Wolf et al, 2009). Also Piscart et al (2005) found Psychomyia pusilla to predominantly colonize river sections of low salinity in the Meurthe river (France), while Bäthe and Coring (2011) recorded Psychomyia pusilla in salinized sections of the river Werra as well. These differences might be related to the permanent exposure to high saline concentrations that may lead to physiological adaptations and hence may increase the salt tolerance of single species (Kay et al, 2001).…”
Section: Indicator Taxa and Salinity Thresholds For Macroinvertebratesmentioning
confidence: 99%
“…In addition to the high salt load, high nutrient concentrations, partly due to inadequately treated sewage and massive morphological degradations have a negative impact on the ecological status of the River Werra. Further information on the currently effective stressors can be found in Bäthe and Coring (2011) in this volume.…”
Section: Introductionmentioning
confidence: 99%